EFFECTIVE WAYS TO DEVELOP WOMEN’S FOOTBALL - O‘ralov Jasurbek Ravshan o‘g‘1i (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes ways to develop women’s football in our country, opinions of experts working in the field. It is aimed at implementing the most effective ways of developing the field